2017 IEEE Virtual Reality (VR) 2017
DOI: 10.1109/vr.2017.7892225
|View full text |Cite
|
Sign up to set email alerts
|

Emotional qualities of VR space

Abstract: The emotional response a person has to a living space is predominantly affected by light, color and texture as space-making elements. In order to verify whether this phenomenon could be replicated in a simulated environment, we conducted a user study in a six-sided projected immersive display that utilized equivalent design attributes of brightness, color and texture in order to assess to which extent the emotional response in a simulated environment is affected by the same parameters affecting real environmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…And can be isolated into two components, he feeling and the judgment of organization, and depends on three standards, in particular the standards of need, selectiveness and consistency, influences the level of immersion in VR The enthusiastic reaction a man has to a living space is overwhelmingly influenced by light, shading and surface as space-production components. To confirm whether this marvel could be recreated in a reenacted environment, the creator led an examination in immersive show that used proportionate outline traits of splendor, shading and surface so as to survey to which degree the enthusiastic reaction in a mimicked domain is influenced by similar parameters influencing genuine environments [5], [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…And can be isolated into two components, he feeling and the judgment of organization, and depends on three standards, in particular the standards of need, selectiveness and consistency, influences the level of immersion in VR The enthusiastic reaction a man has to a living space is overwhelmingly influenced by light, shading and surface as space-production components. To confirm whether this marvel could be recreated in a reenacted environment, the creator led an examination in immersive show that used proportionate outline traits of splendor, shading and surface so as to survey to which degree the enthusiastic reaction in a mimicked domain is influenced by similar parameters influencing genuine environments [5], [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recently, Naz et al (2017) investigated how the visual aspects of a virtual environment influenced emotional qualities and found that color affected warmth, brightness affected spaciousness, and both color and brightness affected excitement. Additionally, Kruijff et al (2016) have investigated how multisensory cues affect emotion in immersive systems and found that surprise could be elicited by low-frequency sounds and back vibrations while happiness could be elicited by wind and smells.…”
Section: Emotionmentioning
confidence: 99%
“…The study found statistically significant main effects of color and brightness (and their interactions) on perception [29]. Figure 2 demonstrates the main effects of color.…”
Section: Quantitative Data Analysismentioning
confidence: 80%
“…Both quantitative and qualitative studies were performed and analyzed. Details of the user study (simulation and study methods, data analysis, results and validation process) were presented at a Virtual Reality Conference and later published [29].…”
Section: Design Data For Sensory Design Elementsmentioning
confidence: 99%